2018
DOI: 10.1155/2018/9232065
|View full text |Cite
|
Sign up to set email alerts
|

Spironolactone Protects against Diabetic Cardiomyopathy in Streptozotocin-Induced Diabetic Rats

Abstract: Spironolactone (SPR) has been shown to protect diabetic cardiomyopathy (DCM), but the specific mechanisms are not fully understood. Here, we determined the cardioprotective role of SPR in diabetic mice and further explored the potential mechanisms in both in vivo and in vitro models. Streptozotocin- (STZ-) induced diabetic rats were used as the in vivo model. After the onset of diabetes, rats were treated with either SPR (STZ + SPR) or saline (STZ + NS) for 12 weeks; nondiabetic rats were used as controls (NDC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 67 publications
2
23
0
Order By: Relevance
“…The RNA concentration was determined using a spectrophotometer (NanoDrop 2000c; Thermo Fisher Scientific, Waltham, MA) with an absorbance of 260 nm. Total RNA was converted to complementary DNA using 5 × All‐In‐One RT MasterMix (ABM, Vancouver, Canada) . Primers (Table ) were synthesized by Sangon Biotech (Shanghai, China).…”
Section: Methodsmentioning
confidence: 99%
“…The RNA concentration was determined using a spectrophotometer (NanoDrop 2000c; Thermo Fisher Scientific, Waltham, MA) with an absorbance of 260 nm. Total RNA was converted to complementary DNA using 5 × All‐In‐One RT MasterMix (ABM, Vancouver, Canada) . Primers (Table ) were synthesized by Sangon Biotech (Shanghai, China).…”
Section: Methodsmentioning
confidence: 99%
“…The granulosa cells were treated for 2 h, 4 h, 8 h, 12 h, 24 h and 48 h which was used for detecting PLCB1 mRNA expression or for 4 h which was used for detecting other genes, and then total RNA was extracted from the cells using TRIzol reagent (Takara, Kyoto, Japan) as described [21]. RNA concentration was determined using a spectrophotometer (NanoDrop 2000c, Thermo Scientific, Waltham, Massachusetts, USA) by absorbance at 260 nm [22]. Then, 1 μg of total RNA was converted to cDNA using 5 × All-In-One RT MasterMix (Abm, Vancouver, Canada) according to the manufacturer’s protocol [22].…”
Section: Methodsmentioning
confidence: 99%
“…RNA concentration was determined using a spectrophotometer (NanoDrop 2000c, Thermo Scientific, Waltham, Massachusetts, USA) by absorbance at 260 nm [22]. Then, 1 μg of total RNA was converted to cDNA using 5 × All-In-One RT MasterMix (Abm, Vancouver, Canada) according to the manufacturer’s protocol [22]. Primers were synthesized by Sangon Biotech (Shanghai, China), and the primer sequences used for genes studied are listed in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“… Fang et al (2018) confirmed that resveratrol might alleviate cardiac oxidative stress, mitochondrial impairment, and myocardial fibrosis in diabetes induced by high glucose. Liu et al (2018) explored the protection of spironolactone against DCM in STZ-induced diabetic rats and concluded that its cardioprotective effects were due to improving mitochondrial dysfunction and reducing cardiac fibrosis, oxidative stress, and inflammation ( Liu et al, 2018 ). Hu et al (2019) demonstrated that the reconstruction of Mfn2 restored mitochondrial membrane potential, inhibited mitochondrial oxidative stress, and ameliorated mitochondrial function in cardiomyocytes treated by high glucose and high-fat through facilitating mitochondrial fusion.…”
Section: Potential Dcm Treatments Targeting Mitochondriamentioning
confidence: 99%